Synthesis of fatty monoester lubricant base oil catalyzed by Fe-Zn double-metal cyanide complex - Raut, Ravindra K.; Shaikh, Mehejabeen; Darbha, Srinivas (Journal of Chemical Sciences, 2014)
Fatty monoester lubricant base oils as high as 96.7 mol% were prepared by reacting methyl oleate with long-chain alcohols viz., 2-ethyl-1-hexanol (C-8-OH), 1-decanol (C10OH) and 1-dodecanol (C12OH) in the presence of a solid Fe-Zn double-metal cyanide (DMC) complex catalyst. Unlike many other acid catalysts, DMC doesn't produce undesired ether side products. The catalyst was reusable in four recycling experiments with little loss in catalytic activity and ester yield. The long-chain esters prepared in the study have the desired physical properties for their application as lubricant base oils.
Keywords: Fatty monoester; Fe-Zn double-metal cyanide (DMC) catalyst; lubricant base oil; transesterification

Stabilization of bis(chlorogermyliumylidene)s within bifunctional PNNP ligand frameworks and their reactivity studies - Sahoo, Padmini; Raut, Ravindra K.; Maurya, Devesh; Kumar, Vikas; Rani, Pooja; Gonnade, Rajesh G.; Majumdar, Moumita (Dalton Transactions, 2019)
The diiminodiphosphine (L-im) and diaminodiphosphines (l-NH and l-NMe) with a bifunctional PNNP ligand framework have been employed to host two [GeCl](+) units leading to the formation of bis(chlorogermyliumylidene) 1-3, respectively. The synthetic route involves a 1:2 stoichiometric reaction between the PNNP ligand and GeCl(2)dioxane and the subsequent addition of two equivalents of chloride abstracting agent. Compound 1 is unstable towards coordinating solvents and Lewis bases, resulting in the displacement of the GeCl unit and the formation of rearranged products 4 and 5. However, the diaminodiphosphine coordinated Ge(ii) bis(monocation)s 2 and 3 proved to be stable and revealed their electrophilic behaviour towards the Lewis bases studied.